Factors Associated With Disordered Eating Behavior Among Adolescent Girls: Screening and Education - Catherine P. Dunn; Joan B. Riley; Kirsten B. Hawkins; Kenneth P. Tercyak (SAGE Publishing, 2022)
Introduction/Objectives: An unhealthy relationship with food can lead to disordered eating in adolescence, highlighting the importance of screening. This study describes the frequency of disordered eating behavior among female adolescents, as well as associated characteristics and health behaviors. Methods: Data are from a multidimensional risk factor screening survey administered at a university medical center's adolescent clinic from 2016 to 2018. The instrument was adapted from existing screening tools such as the Rapid Assessment for Adolescent Preventive Services (RAAPS), the American Medical Association's Guidelines for Adolescent Preventive Services (GAPS), and the Youth Risk Behavior Survey (YRBS). Analysis was limited to self-reported responses provided by females aged 10 to 21 years (N = 915). Statistical analyses included chi-square tests and independent sample T -tests. Results: Of the N = 915 females who reported on disordered eating behavior, n = 57 (6.2%) had engaged in some form of disordered eating behavior within the past 12 months. Disordered eating was significantly associated ( P  < .001) with not consistently wearing a helmet while biking, having tried e-cigarettes, being bullied in the past 30 days, having an adverse childhood experience (ACE), and being African American ( P  = .005). Subgroup analysis of the relationship between disordered eating and bullying, by race, yielded significant findings: disordered eating was more highly associated with being bullied in the past 30 days among African American females ( P  = .038). The relationship between disordered eating and ACE was also significant ( P  < .001) among Caucasian girls when stratified by race. Conclusions: Adolescent risk behaviors often co-occur, and disordered eating behavior may be differentially observed by race. Findings highlight the importance of education and screening to prevent the development of disordered eating, and identify those who may be struggling. These results can be useful to community health education and in healthcare to develop and implement health promotion and eating disorder prevention strategies. Further studies are needed to assess additional factors that promote or protect against disordered eating to improve prevention.